Arbeitsplatzbezogenes Belastungserleben und psychische Gesundheit der Beschäftigten im Gesundheitswesen während der COVID-19-Pandemie: Risiko- und Schutzfaktoren aus der VOICE-Studie - Erim, Yesim; Geiser, Franziska; Beschoner, Petra; Jerg-Bretzke, Lucia; Weidner, Kerstin; Albus, Christian; Baranowski, Andreas M.; Mogwitz, Sabine; Morawa, Eva (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
Background: Healthcare workers have an increased risk of depression and anxiety, and medical staff have faced a wide variety of challenges, especially during the COVID-19-pandemic. The aim of the VOICE study was to investigate risk and protective factors for workplace-related stress experience and mental health. Method: A multicentre, web-based and prospective survey (VOICE study) was initiated in the spring of 2020 by a network of five psychosomatic university clinics (Erlangen, Ulm, Bonn, Cologne and Dresden). More than 25,000 respondents took part in the study at five measurement points. Results: Of 3678 employees examined in a hospital setting during the first wave of the pandemic, 17.4% and 17.8% of physicians, 21.6% and 19.0% of nurses and 23.0% and 20.1% of medical-technical assistants (MTA) were affected by symptoms of depression and anxiety, respectively, to a clinically relevant extent. The most important risk factors for depressive and anxiety symptoms were insufficient relaxation during leisure time, increased alcohol consumption, lower trust in colleagues in difficult work situations and increased fear of becoming ill with COVID-19. Predictors for increased post-traumatic symptoms were increased generalized anxiety and depression as well as increased fear of infecting family members. Sense of coherence, social support, optimism and reward level acted as protective factors. Discussion: The psychological effects of workplace-related stress during the pandemic were found to be significant. Therefore, regular mental health screening and prevention programmes for healthcare workers are indicated.
CRIS-Team Scopus Importer:2024-11-22
Keywords: COVID-19 pandemic; Effort-Reward Imbalance; Healthcare workers; Sense of Coherence; Work-Family Conflict